Hot water extract of oriental melon leaf promotes hair growth and prolongs anagen hair cycle: In vivo and in vitro evaluation - Pi, Long-Quan; Lee, Won-Soo; Min, Sung Hee (Food science and biotechnology, 2016)
Effects of hot water extracts of oriental melon leaves (OML) on promotion of hair growth were investigated. Topical OML extract administration for hair regeneration was investigated using an in vivo model with C57BL/6 mice. Effects of OML extracts on the human hair growth were investigated using a hair follicle organ culture. OML extracts induced a shortened telogen to anagen conversion and promoted hair growth in the C57BL/6 mouse model. Culture of human hair follicles in the presence of OML extracts for 8 days promoted hair growth and prolonged the anagen duration due to induction of hair follicle cell proliferation in the bulb region. OML extracts exert a hair growth promotion effect and, therefore, can be used as a therapeutic agent for prevention of hair loss.